Protective effect of Mori Cortex radicis extract against high glucose-induced oxidative stress in PC12 cells. Issue 10 (3rd October 2019) - You, Sohyeon; Kim, Gun-Hee
ABSTRACT: This study was undertaken to investigate the neuroprotective effect of an ethanolic extract of Mori Cortex radicis (MCR) against high glucose (HG)-induced oxidative damage in PC12 cells. Cell cytotoxicity was examined using MTT and lactate dehydrogenase assays. To examine the antioxidative effects, intracellular reactive oxygen species (ROS) and malondialdehyde (MDA) levels and the activities of antioxidant enzymes were measured. The expressions of apoptosis-associated proteins were assessed. MCR was found to increase the viabilities of HG-induced PC12 cells and to inhibit ROS and MDA production and to promote antioxidative enzyme activities. Furthermore, MCR reduced apoptosis by upregulating p-Akt and Bcl-2/Bax ratio and reducing cytochrome c level. The main flavonoids in MCR were identified by HPLC to be kuwanon G and morusin. These results suggest the antioxidative effects of MCR protect against HG-induced oxidative stress and that MCR has potential therapeutic use for the prevention and treatment of diabetic neuro-degeneration. Graphical abstract: : Protective effect of MCR against HG-induced oxidative stress and its major compounds kuwanon G and morusin